Bram Stoker's Dracula - Stoker, Bram, 1847-1912.; Templesmith, Ben, 1978- (San Diego, Calf. : IDW Publishing, 2009)
"Eisner and International Horror Guild Award nominated writer/artist Ben Templesmith adds his special touch to a true horror classic in this re-presentation of Bram Stoker's Dracula, one of the best-selling and most influential novels of all time."--Back cover.
Keywords: Dracula, Count (Fictitious character) -- Fiction; Dracula, Count (Fictitious character) -- Pictorial works; Vampires -- Fiction